An Irish National Diabetes in Pregnancy Audit: aiming for best outcomes for women with diabetes. Issue 12 (28th February 2019) - Egan, A. M.; Brassill, M. J.; Brosnan, E.; Carmody, L.; Clarke, H.; Coogan Kelly, C.; Culliney, L.; Durkan, M.; Fenlon, M.; Ferry, P.; Hanlon, G.; Higgins, T.; et al.
Abstract: Aims: The purpose of this study was to identify the number of pregnancies affected by pre‐gestational diabetes in the Republic of Ireland; to report on pregnancy outcomes and to identify areas for improvement in care delivery and clinical outcomes. Methods: Healthcare professionals caring for women with pre‐gestational diabetes during pregnancy were invited to participate in this retrospective study. Data pertaining to 185 pregnancies in women attending 15 antenatal centres nationally were collected and analysed. Included pregnancies had an estimated date of delivery between 1 January and 31 December 2015. Results: The cohort consisted of 122 (65.9%) women with Type 1 diabetes and 56 (30.3%) women with Type 2 diabetes. The remaining 7 (3.8%) pregnancies were to women with maturity‐onset diabetes of the young (MODY) ( n  = 6) and post‐transplant diabetes ( n  = 1). Overall women were poorly prepared for pregnancy and lapses in specific areas of service delivery including pre‐pregnancy care and retinal screening were identified. The majority of pregnancies 156 (84.3%) resulted in a live birth. A total of 103 (65.5%) women had a caesarean delivery and 58 (36.9%) infants were large for gestational age. Conclusions: This audit identifies clear areas for improvement in delivery of care for women with diabetes in the Republic of Ireland before and during pregnancy. What's new?: The National Pregnancy in Diabetes Audit was well received in the United Kingdom and outcome improvements have been observed since its initiation Similar processes were not previously in place in Ireland Few women attend a formal pre‐pregnancy care programme Two‐thirds of women experience a caesarean delivery Some 47% infants are admitted to a neonatal intensive care unit The findings will encourage units to develop pre‐pregnancy care programmes for women with diabetes; streamline clinical care and review practices surrounding caesarean delivery